EVALUATION OF THE MEDICAL INTERN’S KNOWLEDGE OF VISCERAL LEISHMANIASIS - Mequi, Fernando Barraca Jesus; Borges, Suellem Luzia Costa; Cabanha, Regiane Santana da Conceição Ferreira (Seven Editora, 2024)
Leishmaniasis belongs to a group of diseases that are still considered public health problems in many countries, this is due to the high global mortality, still very present in the main epidemiological indicators. In Brazil, it is caused by the protozoan Leishmania infantum chagasi and transmitted by sandflies, with the dog being considered the main source of infection in the urban environment, and man the accidental host. It is a serious disease with few therapeutic options and, even when properly treated, has a lethality of about 5%. The state of Mato Grosso do Sul and the city of Campo Grande have suffered, in recent years, environmental changes that may have contributed to the spread of the vector, such as the construction of a gas pipeline, the destruction of areas of the cerrado, as well as the opening of avenues following the watercourses and the felling of vegetation for the construction of popular houses. In view of these changes in the city and the proportion that Visceral Leishmaniasis is gaining, this study sought to understand the knowledge of medical students, in the internship stage, in the city of Campo Grande – MS. This is a quantitative, descriptive cross-sectional study. The sample was by convenience, and 100% of the students were approached during the sessions. The results point to regular knowledge of the students in the internship modality. It is expected that the student reflects on his knowledge about this disease, considering the importance of epidemiology for assertive conduct. DOI:https://doi.org/10.56238/sevened2024.037-042